hsCRP and E-Selectin as Markers of Endothelial Dysfunction in Children with Type 1 Diabetes Mellitus - Nascimento, Antonella Márcia Mercadante de Albuquerque DO (2019)
Introduction: This study investigated the levels of inflammatory biomarkers in healthy children and those diagnosed with type 1 diabetes (T1DM), some of whom were affected by endothelial dysfunction (ED), characterized by increased inflammation and reduced vasodilatation. Methods: Thirty-one T1DM children showing no symptoms of vascular diseases and diagnosed by ultrasound techniques as ED-positive (T1DM-ED) or negative (T1DM), and 58 sex-age-matched healthy children were investigated for circulating levels of E-selectin, s-ICAM and s-VCAM, MMP-9, high-sensitivity C-reactive protein (hsCRP), and IL-6. Results: No differences were observed in s-ICAM, MMP-9, and IL-6 levels between case and control groups. Significantly higher levels of s-VCAM (p= 0.0001) were found in the T1DM (1359.1 ± 273 ng/mL) and T1DM-ED (1358.2 ± 112 ng/mL) groups; (control - 828.5 ± 212 ng/mL). Higher levels of E-selectin (p = 0.001) were found in the T1DM-ED group (331.2 ± 77 ng/mL); (control - 222.2 ± 74 ng/mL). The values of hsCRP were higher (p = 0.002) in the T1DM-ED group (0.36 ± 0.2 mg/L) relative to control (0.15 ± 0.1 mg/L) and T1DM (0.19 ± 0.2 mg/L). The results suggest that E-selectin and hsCRP can be useful markers of ED in children with T1DM.